The Rough Mile: testing a Framework of Immersive Practice - Spence, Jocelyn; Hazzard, Adrian; McGrath, Sean; Greenhalgh, Chris; Benford, Steve (2017)
We present our case study on gifting digital music, The Rough Mile, as an example of a Framework of Immersive Practice, intended for researchers and practitioners in HCI and interaction design. Although immersion is a frequently used term in the HCI and related literatures, we find no definitions or frameworks that are robust enough to capture the full range of multi-sensory, emotional, and cognitive engagement that the richest of these experiences can entail. We therefore turn to the theatrical performance literature to distil a theory-based framework of practices that can apply to interdisciplinary projects as well as works with an entirely aesthetic aim. The design choices and findings of The Rough Mile are presented in terms of this framework, leading to a discussion of the design guidelines that can shape its use in any HCI or interaction design project aiming for a deep, personal engagement through technology.